The Effect of Adrenergic Blockade on the Glucagon Responses to Starvation and Hypoglycemia in Man - Walter, Robert M. (1974)
In an attempt to ascertain whether the sympathetic nervous system modulates glucagon release in man during starvation and hypoglycemia, the influence of alpha and beta adrenergic blockade on glucagon responses was studied in young, healthy men subjected to fasting and insulin-induced hypoglycemia. Six volunteers fasted for 84 h on three separate occasions. Plasma immunoreactive glucagon (IRG), measured initially at 12 h, climbed gradually from mean levels of 54 pg/ml to a zenith of 124 pg/ml at 48 h, with maintenance of these levels for the duration of the fast. The infusion of propranolol or phentolamine throughout the terminal 24 h of the second and third fasts failed to alter the pattern of IRG release. After an overnight fast, five volunteers received insulin intravenously, which evoked a mean rise in plasma IRG levels from 63 pg/ml to a maximum of 256 pg/ml at 30 min. The concurrent administration of propranolol or phentolamine did not modify the glucagon responses to insulin-induced hypoglycemia. These data suggest that the augmented glucagon release in man during starvation or after hypoglycemia is not significantly regulated by signals from the adrenergic nervous system.